Criminal Sanctions for Online Transportation Drivers using Mobile Phones While Driving Based on Article 287 Paragraph (1) of Law Number 22 Of 2009 Concerning Road Traffic and Transportation - Arisman Hia; Ismayani Ismayani; Taufika Hidayati (SEAN Institute, 2026)
The use of mobile phones while driving by online transportation drivers has become a common phenomenon that potentially threatens road safety. This study aims to analyze the implementation of criminal sanctions against online transportation drivers who use mobile phones while driving based on Article 287 paragraph (1) of Law Number 22 of 2009 concerning Road Traffic and Transportation. In addition, this study also examines the obstacles faced in law enforcement and the role of online transportation companies in supervising their drivers. This research uses a juridical normative and juridical empirical approach with a descriptive qualitative method. Data were obtained through literature study and field research including interviews with traffic police officers, legal academics, and online transportation drivers. The results show that the use of mobile phones while driving clearly violates Article 106 paragraph (1) and Article 287 paragraph (1) of Law Number 22 of 2009. However, the existing sanctions have not been fully effective in reducing violations because the penalties are relatively light and law enforcement is still limited. Another factor contributing to violations is the operational system of online transportation applications which requires drivers to respond quickly to incoming orders. Therefore, stronger law enforcement, technological supervision systems, and collaboration between the government, law enforcement agencies, and online transportation companies are needed to reduce violations and improve traffic safety.